Otolith biometry analysis of betong fish, Selar crumenophthalmus (Bloch, 1793) (Teleostei: Carangidae) in Manado Bay, North Sulawesi - Saiful Bahri; Lawrence J. L. Lumingas; Fransine B. Manginsela (Jurnal Ilmiah PLATAX, 2018)
This study aims to examine whether there are differences in the size and shape of otolith both between sexes and between the sampling times of bigeye scad Selar crumenophthalmus in  Manado Bay, North Sulawesi. Most of the otolith sizes and the otolith shape indices do not show any significant differences between left and right, some of which show statistically significant differences such as the otolith length and the indices of the roundness, ellipticity and aspect ratio of female fish at August 2017 and otolith length, otolith width and otolith perimeter of male fish at November 2017. The otolith sizes and shape indices do not differ between sexes but differ between sampling times ie August 2017 and November 2017. Otolith sizes such as length, width, area and perimeter and shape indices such as circularity and rectangularity can be used as indicators of stock determination. Other shape indices of otolith such as form factor, roundness, ellipticity and aspect ratio are not well used as stock determination. Most of the samples showed a negative allometric growth pattern, except in the sample of female fish sampled in November 2017 which showed an isometric growth pattern for all otolith size variables. There is no statistically significant difference in the regression line of the otolith sizes - total length between sexes, but there is a statistically very significant difference in the regression line between sampling times (months) where the otolith size is greater in November 2017 or in other words at the same length of fish, otolith sizes bigger in November 2017 than in August 2017. The otolith sizes and their relationship with the total length of the fish can be used for determining (separating) the stock of bigeye scad Selar crumenophthalmus. There is a possibility that the sample for August 2017 is a different stock with samples from November 2017.Key words: Selar crumenophthalmus, otolith, morphometry, stock identification, Manado Bay ABSTRACTPenelitian ini bertujuan untuk menguji apakah terdapat perbedaan ukuran dan bentuk otolit  baik antar seks maupun antar waktu pengambilan sampel ikan selar betong Selar crumenophthalmus di Teluk Manado Sulawesi Utara. Sebagian besar ukuran serta indeks bentuk otolit tidak menunjukkan perbedaan yang nyata antara kiri dan kanan, beberapa di antaranya menunjukkan perbedaan yang nyata secara statistik misalnya ukuran panjang otolit serta indeks bentuk otolit ‘roundness’, ‘ellipticity’ dan ‘aspect ratio’ pada ikan betina Agustus 2017 dan ukuran panjang otolit, luas otolit dan keliling otolit pada ikan jantan November 2017. Ukuran dan indeks bentuk otolit tidak berbeda antar jenis kelamin tetapi berbeda antar waktu sampling yakni Agustus 2017 dan November 2017. Ukuran otolit seperti panjang, lebar, luas dan keliling otolit serta indeks bentuk seperti ‘circularity’ dan ‘rectangularity’ dapat digunakan sebagai indikator penentu stok. Indeks bentuk otolit lainnya seperti ‘form factor’, ‘roundness’, ‘ellipticity’ dan ‘aspect rasio’ kurang baik digunakan sebagai variable penentu stok. Sebagian besar sampel menunjukkan pola pertumbuhan alometri negatif, kecuali pada sampel ikan betina yang disampling pada November 2017 yang memperlihatkan pola pertumbuhan isometrik untuk semua variabel ukuran otolit. Tidak terdapat perbedaan garis regresi ukuran otolit - panjang total antar seks, tetapi terdapat perbedaan yang sangat nyata garis regresi tersebut antar waktu sampling (bulan) di mana ukuran otolit lebih besar pada bulan November 2017 atau dengan kata lain pada panjang ikan yang sama, ukuran otolit lebih besar pada bulan November 2017 dibandingkan dengan pada bulan Agustus 2017.           Ukuran otolit serta hubungan regresi dengan panjang total ikannya dapat digunakan untuk penentuan (pemisahan) stok ikan selar betong Selar crumenophthalmus. Ada kemungkinan sampel bulan Agustus 2017 merupakan stok yang berbeda dengan sampel bulan November 2017.Kata kunci: Selar crumenophthalmus, otolit, morfometri, identifikasi stok, Teluk Manado